(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. Structural transformation is one of the most effective ways to increase the efficiency of the economy, and therefore ensure the socio-economic development of the country. This issue is especially relevant for Ukraine, which is on the path to membership in the European Union, and whose economy has suffered significant losses as a result of Russian armed aggression. Purpose. The purpose of the article is to systematize the main methodological approaches of scientific schools of economic growth and critically evaluate European practices of structural transformation of the economy. РОЗДІЛ І. Економіка. 1, 2025 29 Methods. The research methodology is based on general scientific principles and basic provisions of economic theory. The work uses methods of analyzing literary sources, synthesizing research results, systematizing scientific data, and systematic analysis of the components of the studied socio-economic systems. Results. According to the research results, the vectors of structural and spatial transformation of EU countries under the influence of economic globalization and strengthening of European integration were established; regularities of spatial differentiation of socio-economic development of individual EU countries were revealed; key problems in ensuring the equalization of spatial development of countries and regions were verified. Conclusions. Based on practical experience and methodological and organizational errors in carrying out structural transformation of the economy of the analyzed EU countries, it is substantiated that further socio-economic development in Ukraine should be based on multi-criteria planning and optimization of the rational use of all available resources.